On Common Ground: Nunavik Inuit in Nunatsiavut, 1763–1942 - Richling, Barnett (Newfoundland and Labrador Studies)

(untitled) (Faculty of Arts, Memorial University, 2022)
“On Common Ground” presents findings of research commissioned by Makivik Corporation in support of Nunavik Inuit claims to rights and interests in neighbouring Nunatsiavut, claims recognized in the 2006 Nunavik Inuit Land Claim Agreement. The original study ex-amined Nunavimmiut patterns of use and occupation in Labrador during the pre- and post-contact eras. Here, the scope is limited to the period after 1763 and focuses on an area spanning eastern Ungava Bay and the Torngat coast. The paper argues that these patterns encompass linked social and economic dimensions of a centuries-deep adaptation to the different subsistence potentials found across the area and are not simply consequences of the rise of colonial institutions.